A structural damping identification technique for coatings on blisks based on improved component mode mistuning model. (June 2020) - Xu, Kunpeng; Sun, Wei; Yan, Xianfei
Abstract: Since the structural damping characteristics of damping coatings are much higher than that of the blisk substrate, the structural damping differences of coatings in each sector directly affect structural damping of the coated blisk. Therefore, for the coated blisk, it is very important to identify the structural damping differences caused by coating. A novel method for structural damping identification of coatings on the coated blisk is proposed. The component mode mistuning (CMM) model is improved for establishing reduced order model (ROM) of coated blisks. In the model, based on the consideration of blisk substrate, the coatings on each sector are decomposed into the mistuned substructures which are independent of each other. Based on this model, the identification formula for structural damping coefficients of coatings on each sector is deduced. A numerical case is given to illustrate the identification procedure. The vibration test methods for obtaining input parameters of damping identification are demonstrated by an actual case. The damping identifications of numerical case and actual case are carried out. The identification results shown that the identification method had high identification accuracy and can be well applied for the damping identification of the hard coating and viscoelastic coating. Highlights: Focusing on coatings on each sector of the coated blisk, a novel structure damping identification method was proposed. Based on consideration mistuning of blisk substrate,  coatings were decomposed into mistuned substructures of tuned blisk. The effectiveness and operability were verified by a numerical case and an actual case. The average deviation rate between the identification results and theoretical values was only 1.16%. This identification method can be used to identify the damping of hard coating and viscoelastic coating.